2016
DOI: 10.1111/aos.13275
|View full text |Cite
|
Sign up to set email alerts
|

High correlation between performance on a virtual‐reality simulator and real‐life cataract surgery

Abstract: Purpose: To investigate the correlation in performance of cataract surgery between a virtualreality simulator and real-life surgery using two validated, objective assessment tools.Methods: Cataract surgeons with varying levels of experience were included in the study. All participants performed and video-recorded three standard cataract surgeries before completing a proficiency-based test on the EyeSi virtual-reality simulator. Standard cataract surgeries were defined as: 1) surgery performed under local anaes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 23 publications
1
53
0
Order By: Relevance
“…() observed fewer complications and a higher level of skill in vitro with more training sessions, whereas Thomsen et al. (,b) found that real‐life performance was significantly improved after proficiency‐based training on the EyeSi Surgical Simulator. Similarly, in vitreoretinal surgery, Deuchler et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() observed fewer complications and a higher level of skill in vitro with more training sessions, whereas Thomsen et al. (,b) found that real‐life performance was significantly improved after proficiency‐based training on the EyeSi Surgical Simulator. Similarly, in vitreoretinal surgery, Deuchler et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several authors have noted that technical skill improvement was transferable from a simulated setting to the operating room (OR), with a high correlation between performance on the virtual‐reality simulator and real‐life surgical performance (Thomsen et al. ,b).…”
Section: Introductionmentioning
confidence: 99%
“…Also in ophthalmology, virtual surgery has been shown to be an important way to adopt surgical skills prior to clinical application (Thomsen et al. ), and the Eyesi surgical simulator is increasingly seen as subject for research in this field.…”
Section: Introductionmentioning
confidence: 99%
“…In light of this, many authors have recommended the use of prior simulation to guide the surgeon in these rare but predictable surgical scenarios, through low-cost surveys of trainee experience, wet and dry laboratory facilities and computer simulation [9][10][11][12][13][14][15][16][17]. Ease of access to a pre-prepared Anterior Vitrectomy Kit with associated adjuncts (AntVitKit) to help with the prompt and appropriate management of VL has been previously described [18].…”
Section: Introductionmentioning
confidence: 99%